IMPLEMENTATION OF MORPHOLOGICAL OPERATION AND BLOB ANALYSIS IN COW’S MILK SOMATIC CELL CALCULATION - Saputra, Wahyu Andi; Fitriana, Gita Fadila; Usada, Elisa; Widodo, Hermawa Setyo (Informatika Pertanian, 2021)
The Indonesian National Standards have established quality standards for fresh cow's milk. One of them is the somatic cell content with a maximum value of 4x105sel/ml. Generally, the content of somatic cells in each milk sample can be calculated manually with the help of a microscope or using a tool called Fossomatic. However, this tool is expensive. The research was conducted using an image processing science approach to detect and calculate the amount of somatic cell content in cow's milk. The operations performed are erosion, dilation, color channel conversion, and labeling. The results showed that the system's accuracy in counting somatic cells reached 85%. From this research, it is expected to be able to count somatic cells with the help of a computer without having to count manually or using a Fossomatic tool.